THE STYLE OF INTROVERT AND EXTROVERT IN ANNOTATED BIBLIOGRAPHY WRITING - Indri Octa Miransyah; Rahmad . Husein; Masitowarni . Siregar (LINGUISTIK TERAPAN, 2023)
Writing is highly essential in school, especially in the English Department, since they must master the fundamentals of writing. Unfortunately, writing is considered as the most challenging of the four English language abilities. Numerous researches discovered that EFL students also experienced a variety of issues with academic writing. This issue must be handled carefully since it has an impact on the teachers’ ability to teach writing in the classroom. In order to overcome these issues, students' personalities must be understood. Students' personalities have a critical effect on their capacity to write. Introvert and extrovert are two personality characteristics that contribute to individual differences. This research used descriptive research where the participants were 8 students who took academic writing class. The students were given a personality questionnaire and the result showed 4 students were introvert and 4 others are extrovert. Then the students were given an annotated bibliography test to find the type and key elements of annotated bibliography used by the students. The writer found that the students used summative annotations and combined annotations. 1 introvert student uses combined annotation and 3 introvert students use summative annotation. Whereas for extrovert students, 2 people use combined annotation and 2 other people use summative annotation. Various obstacles experienced by the students thus effecting their academic writing.